Behavior of protein interfacial films upon bile salts addition - Bellesi, Fernando Alberto (2013)
It was studied the effect of the bile salts on protein interfacial films at oil–water interfaces under simulated duodenal conditions (37 °C, pH 7.0 and 39 mM K2HPO4, 150 mM NaCl and 30 mM CaCl2) in order to develop an interfacial film which could resist the interfacial displacement by the bile salts in the duodenum to control the lipids digestion process, as it could retard the next action of lipase and colipase. The proteins studied were β-lactoglobulin, soy proteins and egg white proteins as well as non-ionic low molecular weight surfactants (Tween 20). The interfacial characterization was done by using a pendant drop tensiometer by analyzing the competitive and sequential adsorption of these components at the oil–water interface. The results demonstrated that soy protein film was particularly more resistant to bile salts displacement.